Do Changes in Fitness Status, Testosterone Concentration, and Anthropometric Characteristics Across a 16-Month Training Period Influence Technical Performance of Youth Soccer Players During Small-Sided Games?. Issue 5 (3rd May 2022) - Rodrigues Lopes, Rafael A.; Aoki, Marcelo S.; Carling, Christopher; Vaz Ronque, Enio Ricardo; Moreira, Alexandre
Abstract: Rodrigues Lopes, RA, Aoki, MS, Carling, C, Vaz Ronque, ER, and Moreira, A. Do changes in fitness status, testosterone concentration, and anthropometric characteristics across a 16-month training period influence technical performance of youth soccer players during small-sided-games? J Strength Cond Res 36(5): 1404–1409, 2022—This study examined the influence of changes in physical capacity, testosterone concentration, and anthropometric characteristics across a 16-month training period on technical performance of youth players during small-sided games (SSG). Thirty-five elite youth players (14.3 ± 0.2 years, 170 ± 6.2 cm, and 61 ± 6 kg) were assessed on 3 occasions (T1, T2, and T3) over the period. A multivariate canonical correlation (MCC) was used to assess the multiple associations between the criterion variable (SSG technical performance) and the predictor variable (physical capacity represented by the Yo-Yo Intermittent Recovery Test Level 1 [Yo-Yo IRT1], testosterone concentration, and anthropometric characteristics). Changes between T1 and T3 were retained for MCC analysis. Multivariate canonical correlation analysis revealed 2 significant functions ( R 2 = 0.42 and 0.36) indicating a significant relationship between predictor and criterion variables. Changes in Yo-Yo IRT1 performance were the main contributor to the predictor variable, whereas the frequency of tackles/interceptions contributed mostly to the criterion variable (SSG technical performance). These results showed that technical performance in SSG was influenced by changes in Yo-Yo IRT1 performance, suggesting the importance of monitoring in conjunction, intermittent exercise capacity, and technical performance in SSG in youth soccer players. In addition, the stability in technical performance during SSG observed over the experimental period suggests that practitioners could use SSG as a tool for systematic real-world monitoring of technical performance rather than isolated practice drills.